Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.5194/bg-20-929-2023
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion of sedimentary rocks as a source of hydrogen peroxide and nutrients to subglacial ecosystems

Abstract: Abstract. Glaciers and ice sheets are renowned for their abrasive power, yet little is known of the mechanochemical reactions which are initiated by abrasion in these environments and their effect on subglacial biogeochemistry. Here, we use sedimentary rocks representative of different subglacial environments and from a previously glaciated terrain, along with subglacial sediments, to investigate the potential for subglacial erosion to generate H2O2 and to release bio-utilisable organic carbon and nutrients (N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…5). Past work has shown that heterotrophic microbial biomass is C-poor yet P-and Nrich (Makino et al, 2003;Godwin and Cotner, 2015) relative to many terrestrial DOM sources and that microbial heterotrophic activity has been linked to a simultaneous assimilation of mineral nutrients (Fenchel and Blackburn, 1979;Martinussen and Thingstad, 1987). While PO 3− 4 is considered to be a preferred and universal source of phosphorus to microbes (Björkman and Karl, 1994), N can be assimilated as NO − 3 /NO − 2 or as the preferred reduced state, NH + 4 /NH 3 (Paul and Clark, 1996;Nyyssönen et al, 2014).…”
Section: Microbiology and Biogeochemical Nutrient Sinksmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Past work has shown that heterotrophic microbial biomass is C-poor yet P-and Nrich (Makino et al, 2003;Godwin and Cotner, 2015) relative to many terrestrial DOM sources and that microbial heterotrophic activity has been linked to a simultaneous assimilation of mineral nutrients (Fenchel and Blackburn, 1979;Martinussen and Thingstad, 1987). While PO 3− 4 is considered to be a preferred and universal source of phosphorus to microbes (Björkman and Karl, 1994), N can be assimilated as NO − 3 /NO − 2 or as the preferred reduced state, NH + 4 /NH 3 (Paul and Clark, 1996;Nyyssönen et al, 2014).…”
Section: Microbiology and Biogeochemical Nutrient Sinksmentioning
confidence: 99%
“…Glacial comminution serves to liberate and in some cases even produce (Telling et al, 2015;Macdonald et al, 2018;Gill-Olivas et al, 2021) redox-sensitive species for subglacial ecosystems. Subglacial bedrock and freshly comminuted sediments can also contain high concentrations of labile nutrients required to support microbial activity, including phosphorus (Föllmi et al, 2009;Hawkings et al, 2016;Hodson et al, 2004), iron (Bhatia et al, 2013;Hawkings et al, 2014;Schroth et al, 2014), and nitrogen (Hodson et al, 2005;Lawson et al, 2014;Wadham et al, 2016;Gill-Olivas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%